Ten years after: a systematic review of the literature on postsecondary education and disability from 2013 to 2022 - Madaus, Joseph; Gelbar, Nicholas; Faggella-Luby, Michael N.; Dukes, Lyman L. (Frontiers in Education, 2024)
This article presents the results of a systematic review of the literature related to postsecondary education and disability published in peer-reviewed articles from 2013 to 2022. It replicates a prior investigation that examined the literature published on this topic between 1952 and 2012. Results indicated a nearly 200% increase in the number of published articles in this 10-year period, and moreover, a nearly 1,400% increase in articles that were based outside of the United States. Articles were published in 636 unique journals. There was also an increase in the number of articles presenting original data. Although most of the articles featured descriptive designs, there was also an increase in articles using mixed methods, single subject, or group designs. Comparisons across the two time periods of investigation are presented, as are implications for the field.